PENGARUH EARNING PER SHARE, PRICE EARNING RATIO, DAN DEBT TO EQUITY RATIO TERHADAP HARGA SAHAM PADA PERUSAHAAN YANG TERDAFTAR DALAM INDEKS LQ-45 DI BURSA EFEK INDONESIA PADA TAHUN 2012-2016 - Meirinaldi Meirinaldi; Fuad Luthfi Zein (Fakultas Ekonomi Universitas Borobudur, 2018)
This study aims to determine the extent of the effect of Return On Assets, Price Earning Ratio and Earning Per Share on Stock Prices. The data used in this study are secondary data collected from financial statements. Data processing method uses regression analysis method with the help of EVIEWS 9.0. Statistical testing uses the individual parameter significance test (t test) and simultaneous significance test (F test). The results showed that simultaneously the return on assets, price earnings ratio and earnings per share variables had a significant effect on the stock price. Partially it shows that analysis 1: earning per share variable has a significant effect on stock prices, while analysis 2: price earning ratio variable has a significant effect on stock prices and in analysis 3: variable debt to equity ratio has no significant effect on stock prices. Keywords: Earning per share, Price Earning Ratio, Debt to Equity Ratio and Stock Price